Prediction of difficult laparoscopic cholecystectomy on the basis of preoperative ultrasonography assessment - Chhaparia, Saurabh; Dewangan, Komal Prasad; Rao Geddam, Srinivasa (International Surgery Journal, 2023)
Background: Laparoscopic cholecystectomy (LC) is widely used for cholecystolithiasis. Abdominal ultrasonography (USG) is the investigation of choice for diagnosis of gall stone and often done before cholecystectomy. It also helps to predict possible complications during peri-operative period. Till now, there is no established definition of difficult LC. Method: Patients diagnosed as cholecystolithiasis confirmed by USG were studied. Nine parameters of abdominal USG had been assessed. Each parameter was divided into two groups, group A and group B based on finding of USG. Total number of USG finding of each group was calculated. Each surgery was assessed and categorise as easy or difficult and co related with total number of USG finding of each group. Results: For difficult LC-group B USG criteria ≥4 with group A USG criterion ≤5 having sensitivity 84.09%, specificity 80.43% and diagnostic accuracy 82.22%. For easy LC-group A USG criterion ≥6 with group B USG criteria ≤3 having sensitivity 80.43%, specificity 84.09% and diagnostic accuracy 82.22%. For easy LC, the mean post-operative stay was 1.57 days and for difficult LC, the mean post operative stay was 2.52 days. Conclusions: Preoperative USG assessment is a good predictor of difficult LC. Thick-walled gall bladder (GB), presence of pericholecystic fluid collection, impacted stone at neck or proximal to neck of GB and contracted GB are good predictors of difficult LC. Gender is not an independent risk factor for difficult LC.